Cumby, Art. A video clip featuring Art's personal fairy story. - Wilson, Lisa (2013)
Art Cumby shares his personal fairy experience from when he was 11 years old, in the Glambrook woods of Heart's Content. Photograph shows a group of boys from the time. Art and his friend, both wearing striped shirts, are the two that were taken by fairies. Image provided by Art.